Common and distinct characteristics associated with self-reported functional status in older patients with cancer receiving chemotherapy. (October 2021) - Torstveit, Ann Helen; Miaskowski, Christine; Løyland, Borghild; Grov, Ellen Karine; Guren, Marianne Grønlie; Ritchie, Christine Seel; Paul, Steven M.; Kleven, Anne Grethe; Utne, Inger
Abstract: Purpose: To evaluate for inter-individual differences in two subjective measures of functional status in older patients (n = 112), as well as to determine which demographic, clinical, and symptom characteristics, and levels of cognitive function, were associated with initial levels and with the trajectory of the two measures. Methods: Functional status was assessed using self-report measures of physical function (PF) and role function (RF) from the European Organization for Research and Treatment of Cancer Core Quality-of-Life Questionnaire at the initiation of chemotherapy and at 1, 3, 6, 9, and 12 months after its initiation. Hierarchical linear modeling was used to assess inter-individual differences in and characteristics associated with initial levels and changes in PF and RF. Results: Characteristics associated with decreases in PF at the initiation of chemotherapy were higher numbers of comorbidities and higher depression, pain, and dyspnea scores. For initial levels of poorer RF, lower Karnofsky Performance Status scores and higher pain and fatigue scores were the associated characteristics. Characteristic associated with worse trajectories of PF was not having had surgery. For RF, worse trajectories were associated with lower cognitive function and higher RF at enrollment. Characteristic associated with both lower initial levels and improved trajectories of PF was having lower performance status at enrollment. Conclusions: Older patients undergoing chemotherapy experience reduced functional performance. Characteristics associated with decrements in PF and RF need to be assessed and interventions implemented to maintain and increase functional status in older oncology patients. Highlights: From initiation of chemotherapy, functional status increased over 12 months. Decrements in cognitive function were associated with poorer role function. Clinicians need to assess functional status in older patients during chemotherapy.